Draft Ocean Acidification Paper For Western Indian Ocean Region - Mwachireya, S; Ndagala, J; Moorgawa, S; Ali, H; Randrianandrasana, J; Kimirei, I; Bhoyroo, V (United Nations Environment Programme, 2018)
Marine ecosystem management and conservation is facing growing challenges from multiple and cumulative stressors (Chapin et al., 2000). Marine ecosystems are threatened by global climate change pressures of such as increased sea surface temperatures, ocean acidification due to increased dissolution of one-quarter of atmospheric carbon dioxide (CO2) dissolution by world oceans annually (Figure 2) causing measurable declines in ocean pH (increase in H+ ions), carbonate ion concentration ([CO32−]) and saturation state (Le Quéré et al., 2015). This process, referred to as ocean acidification (OA), represents a major threat to marine ecosystems (McClanahan et al., 2011).